Upaya Meningkatkan Hafalan AlquranMelalui MetodeTikrar Pada Siswa Kelas VIII Mts Swasta Al-Ikhwan Serapuh - Zaifatur Ridha; Usmaidar Usmaidar; Syafrani Syafrani (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2020)
The observations and interviews at MTS show the low child memorized because students only focused on adding memorized. It surely had a bad effect on the soft memorized sons. Because of the hoses that had been memorized. Furthermore the child has a low motivation to memorize because it has low power. It allows the lazy child to memoriz. Another child who is unable to divide the time between memorizing and incubating the task so that the child grows tired and is lazy to memorize the imi research tubular is to test the effort that dthon's methods are doing. The method used in research is classroom action research (PTK). The object of study (PTK) study of the viii-b class of 31 students of data collection used with wayanway observation, tests and documentation. Based on the results of memorized research on the cycle I shows an increase of 61.5% and the cycle II of 88,5%. So that it can be deduced between the cycle I and cycle II had an increase of 27%.